Bacteriological Characteristics of Contemporary Wood During Soil Deposition in Anoxia Conditions at the Biskupin Archaeological Site (Poland) - Petrifilms™ as an Alternative for Conventional Bacteriological Media - Wyżewski, Zbigniew; Gajewska, Julitta; Rekosz-Burlaga, Hanna; Babiński, Leszek; Waliszewska, Bogusława; Sitarek-Andrzejczyk, Monika (Studia Ecologiae et Bioethicae, 2021)
The paper presents results of quantitative and qualitative analyses of the composition of saprophytic and pathogenic microflora colonising contemporary wood of Scots pine (Pinus sylvestris L.) and oak (Quercus sp.), deposited for eight years in peat soil, under anoxia conditions at two measuring stations located at the fortified settlement of the Lusatian culture in Biskupin. Qualitative determinations of bacteria were performed based on the analyses of their cultural, morphological, physiological, and bio-chemical characteristics. Petrifilms™ and conventional bacteriological media were used for quantitative analyses. Bacteria in the examined wood and surrounding soil were identified as belonging to species, including those of the genera Pseudomonas, Clostridium (Cl. butyricum/beierinckii, Cl. perfringens), Bacillus, Corynebacterium, bacteria from the family Enterobacteriaceae, as well as aerobic and anaerobic cellulolytic bacteria. An important correlation between the standard pour plate method and PetrifilmTM was observed. Petrifilms are an effective alternative, in comparison with traditional methods, for the determination of total bacterial counts for wood samples.